Study of pedestrian flow characteristics in hilly area - Gupta A.; Das V.R.; Pundir N. (My University, 2025)
Walking is also considered to be a clear example of a sustainable mode of transport, especially suited for urban use or relatively shorter distances. Efforts are under way by various local authorities to restore pedestrian access to new developments. The present paper summarizes the results of studies conducted at two hill station in India, i.e., Dharamshala and Slihnla in Himachal Pradesh where longitudinal gradient varies from 3 to 7.5 %. Various pedestrian characteristics like speed and flow were collected from the field, and their correlation was modeled using conservation of mass equation. The speed-density follows a linear relationship whereas the flow-density and flow-speed found out to be following quadratic relationships. Free flow speed varies about 37 % with respect to another flat gradient locations in India and 23. 36 and 31 % with respect to flat gradients locations in Asian. North American and European continents.